Polytetrafluoroethylene tape as a low‐cost hydrophobic substrate for drop‐coating deposition Raman spectroscopy of proteins. (23rd March 2018) - Smith, James; Arnolds, Heike
Abstract: Highly hydrophobic substrates are desirable for drop coating deposition Raman spectroscopy of proteins, because they concentrate the analyte during drying. Most of the commercial substrates used to date are comparatively expensive, whereas thiol or silane functionalisation of surfaces requires a degree of experience not available in a typical biology laboratory. Here, we show that polytetrafluoroethylene tape, commercially available as thread sealing tape, can be stretched across a washer to yield a highly hydrophobic surface, which is thin enough to produce only a very small Raman signal itself. We demonstrate that this simple substrate can be used to yield high‐quality spectra of biomolecules such as human insulin and lysozyme in both native and fibrillated forms. Abstract : Highly hydrophobic substrates are desirable for drop coating deposition Raman spectroscopy of proteins, because they concentrate the analyte during drying. Here, we show that polytetrafluoroethylene tape can be stretched across a washer to yield a highly hydrophobic surface which is thin enough to produce only a very small Raman signal itself. We demonstrate that this simple substrate can be used to yield high quality spectra of biomolecules such as human insulin and lysozyme in both native and fibrillated forms.